The current issues and challenges in the management of floating knee injury: a retrospective study - Kenmegne, Guy Romeo; Zou, Chang; Lin, Yixiang; Yin, Yijie; Huang, Shengbo; Fang, Yue (Frontiers in Surgery, 2023)
Purpose The management of floating knee injuries is still controversial and challenging for trauma specialists. This study aims to evaluate the incidence of the floating knee in lower limb trauma, analyzing the challenges in its management, and factors affecting clinical outcomes. Methods In this mono-center retrospective study, 36 consecutive patients were included. All individuals were diagnosed with an ipsilateral fracture of the femur and tibia, managed surgically according to their fracture pattern (Fraser classification), and the severity of the injury. The timing for each operation was determined based on the general condition of the patient and the local physiological condition of soft tissues. The patients’ clinical outcomes were finally evaluated based on their Karlstrom and Olerud scores and were categorized as excellent, good, acceptable, fair, or poor. Results In this study, the mean follow-up period was 51.39 ± 16.02 months (11–130 months). Incidence of the floating knee was 2.32% in all lower limb traumas. From this number, 16 patients suffered from floating knee injury in the left lower extremity, and 18 in the right lower limb, while in 2 patients the condition was bilateral. The most common injury mechanism was road traffic accidents, accounting for 28 (77.78%) cases. The outcome was as follows; Excellent to good results in 22 (61.11%) cases, acceptable results in 2 (5.56%) cases, and fair to poor results in 12 (33.33%) cases according to the Karlström–Olerud scoring system. The most frequent early complications were wound infection and deep venous thrombosis in 5 (13.88%) of the cases. The most common late complication was common peroneal nerve palsy recorded in 2 (5.56%) cases. Conclusion The presence of important concomitant injuries to the floating knee together with poor soft tissue conditions constituted important factors influencing possible management options and may have led to poorer clinical outcomes.